Determinasi Pengendalian Internal, Ukuran Perusahaan dan Sales Growth Terhadap Tax Avoidance Dengan Ketidakpastian Lingkungan Sebagai Variabel Moderating - Mutiara Saksono Putri; Erma Setiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of internal control, firm size, and sales growth on tax avoidance, with environmental uncertainty as a moderating variable. The research objects are consumer sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period, selected using a purposive sampling method. The data used consists of annual financial reports. Tax avoidance is measured using the Effective Tax Rate (ETR), internal control is assessed based on annual report scores, firm size is measured using the natural logarithm of total assets, and sales growth is calculated based on the annual sales percentage change. Environmental uncertainty is measured based on external fluctuations affecting the business. Data analysis is performed using multiple linear regression with Moderating Regression Analysis (MRA) through SPSS. The results show that internal control does not have a significant effect on tax avoidance, while firm size and sales growth have a significant effect. Environmental uncertainty moderates the relationship between sales growth and tax avoidance but does not moderate the relationship between internal control and firm size with tax avoidance. This study provides insights into the factors influencing tax avoidance in the context of environmental uncertainty.